Proteomic analysis of the hypothalamus of broiler‐type Taiwan country chickens in response to acute heat stress - Tu, Wei‐Lin; Cheng, Chuen‐Yu; Chen, Chao‐Jung; Chan, Hong‐Lin; Wang, Shih‐Han; Tang, Pin‐Chi; Chen, Chih‐Feng; Chen, Hsin‐Hsin; Lee, Yen‐Pai; Chen, Shuen‐Ei; Huang, San‐Yuan (Animal science journal, 2018)
The hypothalamus is a critical center for regulating heat retention or dissipation. This study investigated global protein changes in the hypothalamus of broiler‐type Taiwan country chickens (TCCs) after acute heat stress. Twelve TCC hens aged 30 weeks were allocated to groups subjected to acute heat stress at 38°C for 2 hr without recovery, with 2 hr of recovery, and with 6 hr of recovery; a control group was maintained at 25°C. Hypothalami were collected for protein expression analysis at the end of each time point. The results showed 114 protein spots differentially expressed after acute heat stress. Most of the differentially expressed proteins were involved in cellular processes, metabolism, transport, and cellular component organization. Functional annotation analysis suggested that these proteins were related to cellular defensive responses against heat and oxidative stress, detoxification and toxin export/delivery, cytoskeleton integrity, oxygen transport, and neural development. The results of this study suggest that acute heat stress damages the hypothalamus of broiler‐type TCCs through oxidative stress and provokes a series of responses to stabilize protein structures, degrade misfolded proteins, and remodel cytoskeletons for attenuating the detrimental effects by acute heat stress.